1997
DOI: 10.1557/jmr.1997.0186
|View full text |Cite
|
Sign up to set email alerts
|

Excess Li ions in a small graphite cluster

Abstract: We calculate the optimized geometry and the corresponding electronic structure of Li ions doped in a small graphite cluster with dangling bonds or hydrogen terminations at the edge surrounding the cluster. The calculations imply both covalent and ionic bonds of Li ions to carbon atoms, which may be relevant to explaining the broad signal of the 7 Li NMR Knight shift spectra. Li intercalation, in particular, is possible even at the hydrogen-terminated edges. Because of the finite size effect of the cluster, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…For our calculations we adopted a hexagonal C 54 H 18 cluster in which 18 carbon (C) atoms are terminated by hydrogen atoms at the edge, and the other 36 C atoms are located in the interior region of the cluster, as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For our calculations we adopted a hexagonal C 54 H 18 cluster in which 18 carbon (C) atoms are terminated by hydrogen atoms at the edge, and the other 36 C atoms are located in the interior region of the cluster, as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…The edge state which is partially occupied by electrons at the Fermi level plays an important role in accepting electrons. In fact, we calculated the electronic structure of a Li ion at the edge of a hydrogenterminated nanographite in a previous report 18 (see also Ref. 5) and found that the Li ion has an ionicity of +0.6e at the hydrogen-terminated edge and that the donated electron to the nanographite cluster is distributed over the edge carbon sites.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations